Patient with Recurrent Glioblastoma Responding Favorably to Ketogenic Diet Combined with Intranasal Delivery of Perillyl Alcohol: A Case Report and Literature Review - Santos, Juliana Guimarães; Cruz, Wanise Maria Souza Da; Schönthal, Axel H.; Salazar, Marcela D'alincourt; Fontes, Cristina Asvolinsque Pantaleão; Quirico-Santos, Thereza; Fonseca, Clovis Orlando da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Monoterpene perillyl alcohol (POH) is cytotoxic to temozolomide-resistant glioma cells, regardless of its O6-methylguanine-methyltransferase (MGMT) promoter methylation status. Moreover, adherence to a ketogenic diet (KD) produced successful outcomes in preclinical and clinical studies in the glioma setting.Case Presentation A 54-year-old Caucasian man had a confirmed diagnosis of refractory glioblastoma multiforme (GBM). The immunohistochemical evaluation was negative for methylation, and failed to detect mutations in the isocitrate dehydrogenase (IDH) 1 and 2 genes. In January 2016, the patient was enrolled in a clinical trial combining daily intranasal delivery of POH in combination with a KD. The KD was administered concomitantly with inhalation of POH (55 mg, 4 times a day) in an uninterrupted administration schedule for 3 months.Results The combination treatment was well-tolerated. The nutritional status and anthropometric measurements of the patient were measured. Adherence to the KD was confirmed by measuring the levels of ketone bodies in the urine. Throughout the treatment, a reduced frequency of seizures was observed. After three months of adherence to the treatment, the patient presented with weight loss, reduced body fat, increased water retention, and a slight increase in bone and muscle mass. A follow-up magnetic resonance imaging (MRI) scan after 3 months of treatment revealed marked reduction of the enhancing lesion.Conclusion Intranasal delivery of POH combined with concomitant adherence to a KD appeared to have a beneficial therapeutic effect in a patient with recurrent GBM. Further studies are needed to evaluate the efficacy of this therapeutic strategy in a larger cohort of treatment-refractory GBM patients.
Keywords: ketogenic diet; perillyl alcohol; intranasal administration; glioblastoma multiforme; combination therapy; drug resistance